Manual de atención al cliente para las/los secretarias/os de la corporación de desarrollo social y financiero “Pakarymuy” del Cantón Latacunga. - Chingo Yanchaguano, Wilma Lorena (2013)
This work aims, improve attention to all customers who require the Corporation both internal and external services, in order to optimize the quality of customer service. So were surveyed twenty customers and four administrative staff of different functions. The data obtained is processed, analyzed and the results thrown became the Foundation for the development of the proposal. This research has a social relevance, the need to present a handbook that will serve not only to people immersed in this proposal, if not that will be a guide to be followed by individuals wishing to learn more about a good customer today. This document is an innovative tool that aims to motivate the staff of the Corporation, to the change of attitude and aptitude through theoretical knowledge aimed at improving the service, which will help to strengthen the good image of the institution.